(untitled) (REMUNOM, 2024)
Dear Editors, The study conducted by Meireles and colleagues is illuminating and makes a significant contribution to the discourse surrounding women’s rights in the context of health. It also inspires reflection on the advancements achieved over the years, addressing with respect and sensitivity the positive impact on the physical and mental health of Brazilian women. It is important to emphasize that this analysis was prompted by the amendment of Law No. 8,080, which regulates the Unified Health System - a topic that has been inadequately addressed, particularly in light of the epidemiological data on violence against women and the resultant traumas. In this context, the expansion of rights through Law No. 14,737, enacted on November 27, 2023, represents a crucial step forward for women’s rights, a subject thoroughly elucidated in the article.¹⁻⁶